Re-examining the effectiveness of semantic priming on motor skill performance under pressure - Holmes, D.; Ashford, K. J.; Kinrade, N. P.; Jackson, R. C. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The detrimental effect of pressure on performance is well established (Hill et al., 2010). Priming has been earmarked as a potential intervention that may make performance more robust under pressure. Research has demonstrated that priming can promote concepts such as fluency (Ashford & Jackson, 2010) and activate cortical regions related to automaticity (Beckmann et al., 2012), which appear to lead to superior performance. Following recommendations to replicate priming studies (Kahneman, 2012), the aim was to replicate the study of Ashford and Jackson adding an in-depth cover story for the priming task and a double-blind testing protocol. Methods: 24 skilled male soccer players dribbled a ball as quickly and accurately as possible through a series of 6 cones spaced across 10.5m. Completion time, lateral displacement and probe-reaction time (PRT) were recorded. Utilising a counter-balanced design, individuals completed a semantic priming sentence task exposing them to target words associated with fluent performance (positive condition) or neutral target words (neutral condition) prior to blocks of five trials. Participants performed under low- and high-pressure conditions, both of which included a control condition with no priming. Results: A repeated measures MANOVA revealed non-significant findings for the pressure × condition interaction and main effect of pressure; the main effect of condition was significant (p = .01). Follow-up tests revealed significantly faster task completion times (p = .02) and a tendency towards improved accuracy (p = .06) in the positive prime condition relative to the control. Discussion: Present findings support previous work indicating that semantic priming has a significant effect on skilled performance, even when the researcher and participant are blind to the research expectations and the latter unaware of a priming paradigm. However, the benefits of positive priming were not as pronounced as originally suggested; the difference in time was smaller in magnitude, with no significant change in displacement or PRT. The employment of double blind procedures and measures to prevent conscious association between tasks is warranted to truly establish the efficacy of priming on motor skills. Further research should look to investigate cortical activity to enhance our understanding of priming effectiveness and performance under pressure.